Assessing model-based reasoning using evidence-centered design : a suite of research-based design patterns /: a suite of research-based design patterns. (2017) - Mislevy, Robert J; Haertel, Geneva D; Riconscente, Michelle; Rutstein, Daisy Wise; Ziker, Cindy
No abstract available